Minority Narratives: The Voices of Women Architects from the School of Madrid in Early Democratic Spain (1975-1982) - Josenia Hervás y Heras; Eva Hurtado Torán (Feminismo/s)
Since the mid-19th century and until the 1964 study programme, students at the Madrid School of Architecture had to undergo various entrance exams for university. Women architects in Francoist Spain represented a mere 5% of the profession, a gender gap only overcome many years after the democratic restoration. Yet most of them did not consider feminism as a matter major concern, since the lack of freedom in Spain held greater importance for women that gender issues, which were relegated to a secondary position in public discussions. Starting in 1985, with the development of the Autonomous Regions in Spain and its accession to the European Economic Community, the country underwent a propound transformation. Former generations of women architects would then play a relevant professional role. This paper aims to expose, through the chronological sequence of their graduation—initially in a testimonial and isolated manner and later forming small networks—how their professional careers developed. This chronological approach, as well as a study of their links from a series of conversations with several women architects that studied and/or set their practice during the years of the democratic transition allows us to conclude that they were not only pioneers but also role models and mentors to each other. Their status as a determined minority is reflected in the relationships they established, with friendships and student complicity that accompanied them throughout their lives, as confirmed by their professional collaborations, comments, and vivid memories of their belonging to a group or community.